2011
DOI: 10.1152/ajpendo.00219.2010
|View full text |Cite
|
Sign up to set email alerts
|

Multi-tissue, selective PPARγ modulation of insulin sensitivity and metabolic pathways in obese rats

Abstract: Subramaniam S, Sears DD. Multi-tissue, selective PPAR␥ modulation of insulin sensitivity and metabolic pathways in obese rats. Am

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
68
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 57 publications
13
68
0
Order By: Relevance
“…Our results in monogenic and polygenic rodent models of obesity confirm previous studies showing decreased BCKD protein abundance in adipose of obese and insulin-resistant rats and mice (23,40,42). Both fa/fa obese Zucker rats and obese db/db mice showed decreased RP WAT BCKD protein abundance relative to their lean counterparts, and a moderate obesity-inducing diet (45% kcal from fat) and a more extreme diet (60% kcal from fat) decreased RP WAT BCKD protein abundance in DIO mice.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results in monogenic and polygenic rodent models of obesity confirm previous studies showing decreased BCKD protein abundance in adipose of obese and insulin-resistant rats and mice (23,40,42). Both fa/fa obese Zucker rats and obese db/db mice showed decreased RP WAT BCKD protein abundance relative to their lean counterparts, and a moderate obesity-inducing diet (45% kcal from fat) and a more extreme diet (60% kcal from fat) decreased RP WAT BCKD protein abundance in DIO mice.…”
Section: Discussionsupporting
confidence: 91%
“…Agonism of PPAR␥ in 3T3-L1 adipocytes increased transcript abundances of Bckdhb, Dld, Dbt, and Bcat2 during the course of 3T3-L1 adipocyte differentiation. These results are similar to those of Hsiao et al who showed that adipose tissue from rats treated with PPAR␥ ligand had increased Bckdhb, Dbt, and Dld mRNA expression (23). The results are also reminiscent of the increase in WAT BCAA catabolic pathway transcripts after TZD treatment in humans (40).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In mice, adipose tissue expression of PPARG is down-regulated by fasting and increased when exposed to high fat feeding (Vidal-Puig et al, 1996) supporting data in obese humans demonstrating that a low energy diet can down-regulate adipocyte PPAR γ mRNA expression (Vidal-Puig et al, 1997). Additionally, its association with alterations in insulin sensitivity (Hsiao et al, 2011) and down-regulation of leptin expression in response to agonists (Zhang et al, 1996), both critical neuroendocrine signals/ hormones for orchestrating the central control of ingestive behaviour, are consistent with the notion that PPAR γ may be signifi cant in mediating the response to food and appetite.…”
Section: Peroxisome Proliferator-activated Receptor Gene -A Candidatesupporting
confidence: 73%